Metabolite Profile of Xylem Sap in Cotton Seedlings Is Changed by K Deficiency - Zhang, Xin; Wang, Guo; Xue, Huiyun; Zhang, Jinbao; Wang, Qinglian; Zhang, Zhiyong; Zhang, Baohong (Frontiers in Plant Science, 2020)
Xylem sap, belonging to the plant apoplast, not only provides plant tissues with inorganic and organic substances but also facilitates communication between the roots and leaves and coordinates their development. This study investigated the effects of potassium (K) deficiency on the morphology and physiology of cotton seedlings, as well as pH, mineral nutrient contents, and metabolites of xylem sap. In particular, we compared changes in root-shoot communication under low K (LK) and normal K (NK, control) levels. Compared to control, LK stress significantly decreased seedling biomass (leaf, stem, and root dry weight; stem and root length; root surface area and root volume and levels of K, Na (sodium), Mg (magnesium), Fe (iron), and Zn (zinc) in xylem sap. In all, 82 metabolites in sap analyzed by HPLC-MS/MS showed significant differences between the two conditions; among these, 38 were up-regulated more than 2-fold while the others were down-regulated less than 0.5-fold. In particular, several metabolites found in the cell membrane including 3 cholines (glycerophosphatecholine, 2-hexenylcholine, caproylcholine, and desglucocoroloside) and others such as MDA, α-amino acids and derivatives, sucrose, and sugar alcohol significantly increased under LK stress, indicating that cell membranes were damaged and protein metabolism was abnormal. It is worth noting that glycerophosphocholine was up-regulated 29-fold under LK stress, indicating that it can be used as an important signal of root–shoot communication. Furthermore, in pathway analyses, 26 metabolites were matched to KEGG pathways; L-aspartic acid, which was associated with 10 KEGG pathways, was the most involved metabolite. Overall, K-deficiency reduced the antioxidant capacity of cotton seedlings and led to a metabolic disorder including elevated levels of primary metabolites and inhibited production of secondary metabolites. This eventually resulted in decreased biomass of cotton seedlings under LK stress. This study lays a solid foundation for further research on targeted metabolites and signal substances in the xylem sap of cotton plants exposed to K deficiency.